2023
DOI: 10.1002/anie.202218407
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Lipid Peroxidation by Regulating Cell Membrane Unsaturation To Enhance Chemodynamic Therapy

Abstract: Lipid peroxidation (LPO) is one of the most damaging processes in chemodynamic therapy (CDT). Although it is well known that polyunsaturated fatty acids (PUFAs) are much more susceptible than saturated or monounsaturated ones to LPO, there is no study exploring the effect of cell membrane unsaturation degree on CDT. Here, we report a self‐reinforcing CDT agent (denoted as OA@Fe‐SAC@EM NPs), consisting of oleanolic acid (OA)‐loaded iron single‐atom catalyst (Fe‐SAC)‐embedded hollow carbon nanospheres encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 69 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) staining was performed to detect apoptotic tumor cells (Figure 6a). [26] More TUNEL-positive cells appeared in the ADT@CuSNDs plus laser group, and tumor nuclei were loosely arranged following combination treatment, demonstrating the outstanding antitumor activity of ADT@CuSNDs, which induced a high rate of apoptosis in cancer cells. This result could also be obtained from the analysis of H&E staining (Figure S25, Supporting Information).…”
Section: Methodsmentioning
confidence: 91%
“…Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) staining was performed to detect apoptotic tumor cells (Figure 6a). [26] More TUNEL-positive cells appeared in the ADT@CuSNDs plus laser group, and tumor nuclei were loosely arranged following combination treatment, demonstrating the outstanding antitumor activity of ADT@CuSNDs, which induced a high rate of apoptosis in cancer cells. This result could also be obtained from the analysis of H&E staining (Figure S25, Supporting Information).…”
Section: Methodsmentioning
confidence: 91%
“…Recently, our group developed a single‐atom Fe‐anchored hollow carbon nanosphere loaded with oleanolic acid (OA) and surrounded by erythrocyte membranes (OA@Fe‐SAC@EM), which amplified LPO to enhance tumor ferroptosis by regulating cell membrane unsaturation ( Figure ). [ 49 ] Specifically, OA@Fe‐SAC@EM could effectively catalyze endogenous H 2 O 2 into highly active •OH via the Fenton reaction in the TME, enabling erythrocyte membrane disruption and OA release. The OA greatly upregulated the expression of Acyl‐CoA synthetase long chain family member 4 (ACSL4) and subsequently increased the amount of polyunsaturated fatty acids (PUFAs) on cell lipid membranes.…”
Section: Biomedical Applications Of Sazymesmentioning
confidence: 99%
“…[89] Chen et al reported an oleanolic acid (OA)-loaded Fe SAzyme for self-reinforcing chemodynamic therapy. [49] To meet the biomedical needs, the SAzyme was coated with RBC membrane to obtain the OA@Fe-SAC@EM nanoparticles (NPs). The dynamic light scattering (DLS) results showed that RBC membrane shell significantly improved the stability of Fe SAzymes under physiological conditions.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…A recent study by Zhu et al focused on amplifying such lipid peroxidation to maximize the CDT-induced damage to cancer cells. 133 The novelty lies in the exploitation of the properties of polyunsaturated fatty acids (PUFAs) that are particularly more susceptible to ROS-induced lipid peroxidation compared to saturated and monounsaturated fatty acids. To increase the fatty acid unsaturation in cancer cell membranes, they developed erythrocyte membrane-encapsulated hollow carbon nanospheres that contained Fe single-atom catalysts and oleanolic acid.…”
Section: Strategies To Improve Cdt Efficiencymentioning
confidence: 99%